POLA PENYEBARAN PENYAKIT MENULAR BERDASARKAN KABUPATEN/KOTA DI JAWA TIMUR MENGGUNAKAN ANALISIS KORESPONDENSI - Triyani Hendrawati; Riska Tiana; Soffy Mulyani; Silma Minnatika (LPPM Universitas Bina Bangsa, 2023)
Infectious diseases are a problem that is still a challenge and has not been resolved in Indonesia. The number of infectious disease cases continues to increase every year in Indonesia. Infectious diseases that are still a problem in Indonesia include tuberculosis (TB), pneumonia and leprosy (Leprosy). Identification of infectious disease endemic areas is an important issue in the health sector, the average rate of people with physical disabilities and deaths originating from infectious diseases. Indonesia, as a country consisting of 34 provinces, including East Java as one of the provinces that has a high rate of infectious disease cases. Therefore, research was conducted using correspondence analysis which aimed to determine the pattern of infectious disease trends and grouping districts / cities in East Java Province based on similarities between the spread of disease sufferers in each district / city. This type of research uses quantitative methods with secondary data obtained from the Central Bureau of Statistics of East Java Province. The results of correspondence analysis show that the spread of pneumonia and tuberculosis in East Java Province has a relative tendency to almost all regencies/cities in East Java, while the spread of leprosy is closer to Sampang Regency. From this research, it can be used to supervise and control infectious diseases in districts / cities in East Java Province, so that the government can adjust policy formulation and actions to prevent an increase in infectious disease cases in East Java